1999
DOI: 10.1177/000348949910800607
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxides in Middle Ear Fluid after Acute Otitis Media in Guinea Pigs

Abstract: Oxygen free radical damage has been demonstrated in the middle ear mucosa of a guinea pig model of acute otitis media (AOM). Potential sources of free radicals include both neutrophils responding to infection and Streptococcus pneumoniae, a common AOM pathogen. This project was conducted to examine the middle ear fluid in a guinea pig model of AOM for evidence of elevated lipid peroxide (LPO) as a marker of free radical damage. Twenty-one guinea pigs were injected transtympanically with bacteria into the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 5 publications
0
23
1
Order By: Relevance
“…It is important to note, however, that freezing was also used in the storage of samples during previous experiments in our laboratory, experiments that did demonstrate a difference in free radical-mediated damage. [2][3][4][5][6] Although this study showed no statistically significant difference in LPO content between healthy and diseased tissue in chronic rhinosinusitis, perhaps the difference, if it exists at all, is smaller and therefore more difficult to detect than that which has been shown in OM. While the neutrophil respiratory burst is a part of the inflammatory response and contributes to free radical formation in OM and rhinosinusitis, S pneumoniae, the other source of free radicals in OM, may not play as large a role in chronic rhinosinusitis.…”
Section: Commentcontrasting
confidence: 62%
See 1 more Smart Citation
“…It is important to note, however, that freezing was also used in the storage of samples during previous experiments in our laboratory, experiments that did demonstrate a difference in free radical-mediated damage. [2][3][4][5][6] Although this study showed no statistically significant difference in LPO content between healthy and diseased tissue in chronic rhinosinusitis, perhaps the difference, if it exists at all, is smaller and therefore more difficult to detect than that which has been shown in OM. While the neutrophil respiratory burst is a part of the inflammatory response and contributes to free radical formation in OM and rhinosinusitis, S pneumoniae, the other source of free radicals in OM, may not play as large a role in chronic rhinosinusitis.…”
Section: Commentcontrasting
confidence: 62%
“…1 Free radical-mediated damage has been characterized in the pathogenesis of more than 100 disorders including stroke, atherosclerosis, myocardial infarction, autoimmune diseases, and nervous system disorders. 1 Studies in our laboratory have implicated free radicals in otitis media (OM) in animal models [2][3][4][5] and humans. 6 Neutrophils, in their respiratory burst, and Streptococcus pneumoniae, the most common pathogen in acute OM, 7 are thought to generate the damaging species in this infection.…”
mentioning
confidence: 99%
“…Furthermore, when compared the AOM and AT groups, there was statistically significant difference between the groups (Table 1). Many investigators, both experimental [16][17][18][19][20] and human [21][22][23][24][25] studies have measured lipid peroxidation levels in AOM and acute or chronic tonsillitis. These studies also demonstrated that increased oxidative stress in the both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MDA, an end product of membrane lipid peroxidation, is one of the most widely used markers for free radical mediated damage. Many investigators have measured lipid peroxidation levels in AOM and acute or chronic tonsillitis in both experimental [ 25 , 26 , 27 , 28 , 29 ] and human [ 30 , 31 , 32 , 33 , 34 ] studies. These studies also demonstrated that increased oxidative stress in the both diseases.…”
Section: Discussionmentioning
confidence: 99%